EFFICIENCY ANALYSIS OF TURKISH BANKING SYSTEM - YILMAZ, Ayşe Altıok (Journal of Advanced Studies in Finance, 2013)
The efficiency of the banking system is one of the most important issues in the financial market because the efficiency of banks can affect the stability of the banking industry and thus the effectiveness of the whole monetary system. The aim of this paper is to analyze the efficiency of the banking system in Turkey between the years 2007-2010. The efficiency scores of the 30 commercial banks are measured by using Data Envelopment Analysis (DEA) between the years 2007-2010. The effects of the 2008 financial crisis on the Turkish banking system efficiency and the efficiency score differences of domestic and foreign bank subgroups operating in Turkey are also examined in this paper.